Application for Selling Food and Beverage Products in CSDW Restaurants Based on Android: Aplikasi Penjualan Produk Makanan dan Minuman di Rumah Makan CSDW Berbasis Android - Muhammad Manggarai Rameli Sutikno; Mohammad Suryawinata (Academia Open, 2020)
CSDW is one restaurant that sells various kinds of fish dishes. As the development of the mobile application finally impacts on various areas of our lives. One of them is the trade sector. Considering that many customers are lazy to go out and buy food, researchers take the initiative to build online ordering applications at CSDW restaurants online with smartphones to make it easier for customers. The aim of this study is to produce an Android-based sales application for ordering food and transactions that can be done anywhere without having to come and queue, accompanied by images to be easily understood.Data collection techniques used are by observing and studying literature. Researchers hope to be able to help customers to be able to facilitate food and transactions easily without having to queue and come to the place.The results of the study are that it makes it easier for customers to buy food quickly and efficiently without having to wait in line or come to the CSDW restaurant.